2010
DOI: 10.1007/s12665-010-0638-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous rainfall on surrounding rock-initial support system of shallow decomposed-rock tunnel

Abstract: A case study is presented to identify the influence of continuous rainfall on surrounding rock-initial support system of shallow decomposed-rock tunnel. From March 21 to April 29, 2006, rainfall with intensities ranging from \10 mm/day to [25 mm/day fell several hours every day, resulting in the collapse of the tunnel crown after the initial support of the surrounding rock in a part of shallow tunneling bench sections of Xiang-an Subsea Tunnel, located in Xiamen, Fujian, China. The applied calculation method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The model captures the salient features of shallow tunnels in partially saturated ground, for example, the effect of suction on the deformation and stability of the tunnel. Tunnel failures are often caused by inundation as a result of heavy rainfall (Grasso et al, 2003;Xu & Ning, 2010;Alija et al, 2014) or outfall of pumps. This wetting-induced face failure can be fairly well described by the numerical model.…”
Section: Discussionmentioning
confidence: 99%
“…The model captures the salient features of shallow tunnels in partially saturated ground, for example, the effect of suction on the deformation and stability of the tunnel. Tunnel failures are often caused by inundation as a result of heavy rainfall (Grasso et al, 2003;Xu & Ning, 2010;Alija et al, 2014) or outfall of pumps. This wetting-induced face failure can be fairly well described by the numerical model.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the calculation model is degenerated into the axisymmetric circular tunnel which is homogeneous and isotropic. And then its analytic solution of equivalent Young's modulus and equivalent lateral confinement pressure coefficient of surrounding rock is expressed as follows [8]:…”
Section: Principle Of Pnbmmentioning
confidence: 99%
“…Shin et al [4] studied the effect of groundwater flow on a deep circular tunnel with an elastic-plastic homogeneous foundation, and the results showed that groundwater flow at the tunnel wall affects radial and axial deformations. Xu and Li [5] studied the effect of continuous rainfall on the stability of shallow weathered rock tunnels. The results show that the infiltration of rainwater makes the surrounding rock of shallow weathered rock tunnels soften continuously due to continuous rainfall, resulting in the stiffness and confining pressure of surrounding rock coefficient decreases.…”
Section: Introductionmentioning
confidence: 99%